Flying Geese of Japan: Asian Electronic Industry - Norimah Rambeli, Ramli; Dayang Affizzah, Awang Marikan; Mee-Sing, T; Kai-Lynn, K (OMICS International, 2016)
Although Japan is known as the largest electronics goods manufacturer, many Japanese companies are facing high cost production due to limited resources. Some Asian countries have been proven to surpass Japan due to their low cost production and cheaper labour. This study analyse the development of Asian leading electronic industries and validity Japan as the flying geese in Asian electronic industries. The empirical result shows that all Asian countries are divergence except Italy, India, United Kingdom and Indonesia. The study suggest that each of the Asian convergence countries should cooperate, give their obligation and commitment to track in the same direction of economic structure, political will and the income distribution of a country. This action could promote economic integration between Asian countries as a whole.